Synthesis of a novel magnetic polyacrylamide coagulant and its application in wastewater purification - Zhou, Zheng (Water science and technology : a journal of the International Association on Water Pollution Research, 2017)
In this study, a novel magnetic polyacrylamide (PAM) coagulant based on the core of magnetite (Fe3O4), with oleic acid serving as modifier and acrylamide as monomer, was synthesized to remove suspended solids in kaolin-suspended water. The composites were characterized by Fourier transform infrared spectroscopy, X-ray diffraction, thermo gravimetric analysis and scanning electron microscopy. The results demonstrated that 82.8% of turbidity removal rate was obtained in 5 min of static settling in simulated kaolin-suspended water. This proved to be superior to that of PAM and poly aluminum chloride. Also confirmed in this study was the fact that zeta potential was significantly correlated with turbidity removal